Comparative Study of Static Stress on Bearing 6207: Analysis Based on Manufacturer Brands and Its Impact on System Performance - Dwilestari, Charisma; Feriyanto, Dafit (Journal of Advanced Industrial Technology and Application, 2023)
This research provides a thorough examination of ball bearings from various brands, with a specific focus on 6207 type bearings, using ANSYS simulation software. The bearings under study are sourced from five different brands: KOYO, NSK, Nachi, NTN, and SKF. The study includes a series of tests, with a primary emphasis on assessing static stress when subjected to a 1000 MPa pressure load. Key parameters evaluated in these tests encompass total deformation, equivalent stress, bearing life, and safety factor. The findings from the analyses reveal significant differences among the tested bearings. Notably, KOYO brand bearings demonstrate superior performance compared to their counterparts, characterized by reduced levels of deformation and stress. However, it’s important to acknowledge that each brand of bearings possesses distinctive characteristics, comprising both strengths and weaknesses, contingent upon the specific application context. In conclusion, this study underscores the critical importance of thorough testing and analysis in the process of selecting bearings tailored to precise operational requirements. The research highlights the exceptional performance of KOYO bearings under the examined conditions, while also emphasizing the necessity for a nuanced decision- making process that takes into account diverse user preferences and varied application demands.